2017
DOI: 10.12688/f1000research.10862.1
|View full text |Cite
|
Sign up to set email alerts
|

Yin and yang of interleukin-17 in host immunity to infection

Abstract: The interleukin-17 (IL-17) family cytokines, such as IL-17A and IL-17F, play important protective roles in host immune response to a variety of infections such as bacterial, fungal, parasitic, and viral. The IL-17R signaling and downstream pathways mediate induction of proinflammatory molecules which participate in control of these pathogens. However, the production of IL-17 can also mediate pathology and inflammation associated with infections. In this review, we will discuss the yin-and-yang roles of IL-17 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 177 publications
3
51
0
Order By: Relevance
“…In contrast, later IL-17 neutralization did not result in severe disease progression and only slightly increased HN878 burden at the time of harvest (Figure 2, A-C). While Th17 cells are a major source of IL-17 in HN878 infection, γδ T cells can also produce IL-17 early after HN878 infection (22). Consistent with these findings, γδ T cells were the major lymphocytic source of IL-17 in HN878 lungs despite accumulation of CD4 + and CD8 + T cells producing IL-17 in the lungs of HN878-infected mice ( Figure 2D).…”
Section: Il-17 Limits Hif1α Expression In Vitro While Il-17 Neutralisupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, later IL-17 neutralization did not result in severe disease progression and only slightly increased HN878 burden at the time of harvest (Figure 2, A-C). While Th17 cells are a major source of IL-17 in HN878 infection, γδ T cells can also produce IL-17 early after HN878 infection (22). Consistent with these findings, γδ T cells were the major lymphocytic source of IL-17 in HN878 lungs despite accumulation of CD4 + and CD8 + T cells producing IL-17 in the lungs of HN878-infected mice ( Figure 2D).…”
Section: Il-17 Limits Hif1α Expression In Vitro While Il-17 Neutralisupporting
confidence: 78%
“…IL-17 has a well-documented role in the induction of chemokines that mediate neutrophil recruitment for pathogen control (22). Thus, we determined whether IL-17 neutralization affected neutrophil accumulation in HN878-infected lungs.…”
Section: Il-17 Neutralization Leads To Mdsc Accumulation and Decreasementioning
confidence: 99%
“…Th17 cells are best known for their roles in immunosurveillance of mucosal barrier surfaces and in many autoimmune and inflammatory diseases. The role of IL-17 during intracellular and viral infections remains unclear, because there is evidence both for protective and pathological roles [26,27]. Finally, we observed that a reduced frequency of CD8 and CD4 T cells producing TNFα at baseline is associated with protection from mortality upon virus infections ( Figure 3C and F).…”
Section: Associated With Increased Risk Of Death After Virus Infectionmentioning
confidence: 77%
“…To date, no cases of reactivation of latent tuberculosis (TB) infection (LTBI) were observed. 17 However, reports that IL-17A-producing γδT cells and CD4 + T cells might have protective or pathologic roles during different phases of Mycobacterium tuberculosis infection 15,16,[18][19][20][21][22] emphasize the need to further explore the role of IL-17A in this context.…”
mentioning
confidence: 99%